Prediction of Insufficient Beta-Lactam Concentrations in Extracorporeal Membranous Oxygenation Patients - Amandine Polain; Julie Gorham; Immacolata Romeo; Mirko Belliato; Lorenzo Peluso; Francesco Partipilo; Hassane Njimi; Alexandre Brasseur; Frederique Jacobs; Jacques Creteur; Maya Hites; Fabio Silvio Taccone (Microorganisms, 2021)
Background: The aim of this study was to identify predictors of insufficient beta-lactam concentrations in patients undergoing extracorporeal membrane oxygenation (ECMO). Methods: Retrospective analysis of all patients receiving ECMO support and treated with ceftazidime or cefepime (CEF), piperacillin/tazobactam (TZP), or meropenem (MEM). Trough drug concentrations (Cmin) were measured before the subsequent dose, according to the decision of the attending physician. Insufficient drug concentrations were identified if Cmin was below the clinical breakpoint of Pseudomonas aeruginosa. Results: A total of 222 Cmin (CEF, n = 41; TZP, n = 85; MEM, n = 96) from 110 patients were included; insufficient concentrations were observed in 26 (12%) antibiotic assessments; 21 (81%) of those occurred during MEM therapy. Insufficient Cmin were associated with a shorter time from initiation of antibiotics to measurement, a lower single dose of antibiotic, a higher creatinine clearance (CrCL), lower sequential organ failure assessment (SOFA) scores, and less use of continuous renal replacement therapy (CRRT) when compared to others. Conclusions: Insufficient broad-spectrum beta-lactam concentrations were observed in 12% of drug measurement during ECMO therapy. Higher than recommended drug regimens could be considered in the very early phase of therapy and in those patients with augmented renal clearance and with less severe organ dysfunction.